1998
DOI: 10.1007/s003390051288
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of tetraethoxysilane (TEOS) on Si(111)-(7×7)

Abstract: We report results of a combined scanning tunneling microscopy and X-ray photoelectron spectroscopy study on the thermal decomposition of tetraethoxysilane (TEOS), a precursor for SiO 2 formation by chemical vapor deposition, on Si(111)-(7 × 7). Annealing after predominantly dissociative adsorption at room temperature, where triethoxysiloxane and ethyl groups are the main adsorbate species, leads to further decomposition with various products evolving, including diethoxysiloxane and further ethyl groups. This g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Tri and diethoxysiloxanes and a Si-O-Si network were formed during the reaction. Thus, the hydrophobization of the filter paper was established through the interaction with the hydroxyl groups of cellulose [37][38][39].…”
Section: Silylation Of Cellulose With Teosmentioning
confidence: 99%
“…Tri and diethoxysiloxanes and a Si-O-Si network were formed during the reaction. Thus, the hydrophobization of the filter paper was established through the interaction with the hydroxyl groups of cellulose [37][38][39].…”
Section: Silylation Of Cellulose With Teosmentioning
confidence: 99%
“…It has been reported that thermal decomposition of TEOS, i.e., by scission of the residual O-C bonds and reorientation of the Si-O bonds with the remaining Si = O fragments, represents the very beginning of SiO 2 phase formation. 21 In this study, the supply rate of TEOS or the SiO 2 content would essentially affect the structure.…”
Section: Resultsmentioning
confidence: 94%
“…where the TEOS monomer implemented a nonlinear polymerization and formed a three-dimensional structure due to its tetrafunctional structure. The structure of the original materials would basically determine the final structure and amorphous nature of nanowires [8,14,21].…”
Section: Resultsmentioning
confidence: 99%